Translating Project Achievements into Strategic Plans: A Case Study in Utilization-Focused Evaluation - Ricardo Ramírez; Galin Kora; Dal Brodhead (Journal of MultiDisciplinary Evaluation)
Background: Utilization-focused evaluation (UFE) is a decision-making framework intended to design and implement evaluations that get utilized. In this case study, the UFE approach was applied to the evaluation of a youth training and employment program in Kenya.